Orientation toward life among displaced female students and survivors of kidnapped Yazidis (a comparative study) - Jamil, Ibtisam Mohammed Saeed; Hamad, Abdulqader Hussein (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Life Orientation is one of the modern concepts in positive psychology, which is the individual's vision of the bright aspects of life with hope, optimism, happiness, and satisfaction with oneself and society, and the formation of social relationships with others to achieve psychological and social harmony. The researchers used the descriptive method, and the research sample consisted of (255) students for the academic year (2022-2023), with a rate of (200) students from among the school girls affiliated with the representative of the Ministry of Education in Erbil, who were selected randomly, and (55) kidnapped Yazidi survivor students living in the refugee camps in the Dohuk governorate, were chosen by the intentional method. The researchers built the life orientation scale as a tool for data collection.